2018
DOI: 10.17261/pressacademia.2018.779
|View full text |Cite
|
Sign up to set email alerts
|

The influence of company size, company profit, solvency and CPA firm size on audit report lag

Abstract: Purpose -To reveal the effect of each of company size, company profit, solvency and the size of public accountant on audit report lag for the infrastructure, utility and transportation sectors listed on the Indonesian Stock Exchange. Methodology -The population of this research are infrastructure, utility and transportation companies that are listed on and supervised officially by the Indonesian Stock Exchange from 2013-2015. The technique used for choosing the sample was purposive sampling. The sample consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 12 publications
1
8
2
5
Order By: Relevance
“…This finding is in tandem with Research Journal of Finance and Accounting www.iiste.org ISSN 2222-1697 (Paper) ISSN 2222-2847 (Online) Vol.10, No.24, 2019 53 those of Sakka and Jarboui (2016); Arowosegbe et al (2017); and Rahmawati (2018) who also reported that firm size has a significant effect on timeliness of financial reports. The finding, however, does not tally with those of Alkhatib and Marji (2012); Ibadin and Afensimi (2015); Mutiara, et al (2018) whose reports indicated an insignificant effect of firm size on timeliness of financial reports.…”
Section: Discussion Of the Findingscontrasting
confidence: 56%
See 1 more Smart Citation
“…This finding is in tandem with Research Journal of Finance and Accounting www.iiste.org ISSN 2222-1697 (Paper) ISSN 2222-2847 (Online) Vol.10, No.24, 2019 53 those of Sakka and Jarboui (2016); Arowosegbe et al (2017); and Rahmawati (2018) who also reported that firm size has a significant effect on timeliness of financial reports. The finding, however, does not tally with those of Alkhatib and Marji (2012); Ibadin and Afensimi (2015); Mutiara, et al (2018) whose reports indicated an insignificant effect of firm size on timeliness of financial reports.…”
Section: Discussion Of the Findingscontrasting
confidence: 56%
“…In order to avoid conflict of interest, the principal can establish monitoring system including financial statement audit which will help to reduce information asymmetry and protect the interest of the principal and all shareholders by providing assurance that financial statement prepared by management reflects the 'true' economic condition and operating results of the entity. Mutiara, Zakaria and Anggraini (2018) reveal the effect of each of company size, company profit, solvency and the size of public accountant on audit report lag for the infrastructure, utility and transportation sectors listed on the Indonesian Stock Exchange. The population of the study are infrastructure, utility and transportation companies that are listed on and supervised officially by the Indonesian Stock Exchange from 2013-2015.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Sehingga, walaupun perusahaan memiliki utang, tetapi perusahaan masih mampu melakukan pembayaran utangnya, maka dari itu informasi mengenai utang ini tidak terlalu diprioritaskan. Hasil riset sama dengan penelitian sebelumnya yang diteliti oleh Mutiara, Zakaria, & Anggraini (2018) yang menunjukkan bahwa ketepatan waktu penyampaian laporan keuangan tidak dipengaruhi secara signifikan oleh variabel solvabilitas.…”
Section: Solvabilitas Terhadap Ketepatan Waktu Penyampaian Laporan Keunclassified
“…Each issuer or public company whose registration statement has become effective must submit an annual report to Indonesian Capital Market Board (BAPEPAM) submitted a maximum of 4 months after the publication of the internal financial report. (Mutiara et al 2018). For issuers or public companies listed on stock exchanges in Indonesia and other countries' stock exchanges, where the deadline for submitting the annual report is different from the provisions set by capital market authorities in other countries (Farag et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The influencing variable is the size of the company and the company that reported the loss. Mutiara, et al (2018) conducted a study on Audit Lag the result of multivariate research shows that the four factors simultaneously have an effect on Audit Lag, but the consistent effect is book year and reporting loss. The result of the research shows that the variable Company Size, Company Profit, Solvency and CPA Firm Size has a significant effect On Audit Report Lag.…”
Section: Introductionmentioning
confidence: 99%